2023
DOI: 10.1136/bmj-2022-073435
|View full text |Cite
|
Sign up to set email alerts
|

Denosumab and incidence of type 2 diabetes among adults with osteoporosis: population based cohort study

Abstract: Objective To estimate the effect of denosumab compared with oral bisphosphonates on reducing the risk of type 2 diabetes in adults with osteoporosis. Design Population based study involving emulation of a randomized target trial using electronic health records. Setting IQVIA Medical Research Data primary care database in the United Kingdom, 1995-2021. Participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 51 publications
0
11
1
Order By: Relevance
“…A post hoc analysis of the FREEDOM trial indicated no significant effect of denosumab on reducing diabetes risk (relative risk, 0.85; 95% CI, 0.61-1.17), with potential underpowering hindering conclusive findings. In contrast, a recent retrospective cohort study in the UK suggested reduced risk of diabetes associated with denosumab use compared with bisphosphonate use (HR, 0.68; 95% CI, 0.52-0.89) . However, confounding by indication may not have been completely eliminated in that study because factors such as kidney function and upper gastrointestinal tract diseases may be associated with the selection of denosumab or bisphosphonates.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…A post hoc analysis of the FREEDOM trial indicated no significant effect of denosumab on reducing diabetes risk (relative risk, 0.85; 95% CI, 0.61-1.17), with potential underpowering hindering conclusive findings. In contrast, a recent retrospective cohort study in the UK suggested reduced risk of diabetes associated with denosumab use compared with bisphosphonate use (HR, 0.68; 95% CI, 0.52-0.89) . However, confounding by indication may not have been completely eliminated in that study because factors such as kidney function and upper gastrointestinal tract diseases may be associated with the selection of denosumab or bisphosphonates.…”
Section: Discussionmentioning
confidence: 77%
“…However, while some clinical evidence suggests denosumab may be positively associated with glycemic parameters, such as fasting plasma glucose and homeostatic model assessment for insulin resistance, its effect on reducing diabetes risk remains unclear . A previous post hoc analysis of the FREEDOM trial indicated no statistically significant effect of denosumab in lowering diabetes risk, but limitations due to potential issues of being underpowered and having a small number of diabetes cases make the findings of the trial inconclusive . In contrast, a recent retrospective cohort study in the UK suggested lower diabetes risk associated with denosumab use compared with bisphosphonate use, despite potential confounding bias by indication .…”
Section: Introductionmentioning
confidence: 99%
“…[ 37,38 ] For example, bone morphogenic proteins derived from the bone matrix and osteoprotegerin secreted by osteoblasts have been shown to regulate insulin secretion. [ 39,40 ] Observational studies examining the effect of denosumab on glucose parameter improvement [ 41 ] and T2DM risk reduction [ 42 ] also support osteoprotegerin may play a role in mediating the relationship, but there has not been a clinical trial on denosumab with glycemic traits as the intended outcome in those with diabetes. Considering the intricate interplay between bone and glucose metabolism, depicting a complete picture of the crosstalk between these two systems is challenging and requires further research.…”
Section: Discussionmentioning
confidence: 99%
“…The death date recorded in the IMRD is linked to the NHS; thus, a change in vital status to “dead” is immediately updated in the person's electronic health record. The secondary outcomes were incident hypertension, 25 T2DM, 26 VTE (pulmonary embolism and deep vein thrombosis), CVD (myocardial infarction [MI] and stroke), 27 and any cancer (lung, breast, colorectal, prostate, head and neck, and other cancers) 28 identified by Read codes during the five‐year follow‐up period. VTE was defined as a recorded Read code of VTE with a prescription of anticoagulant medication.…”
Section: Methodsmentioning
confidence: 99%